2018
DOI: 10.14746/ikps.2017.19.08
|View full text |Cite
|
Sign up to set email alerts
|

Radzenie sobie ze stresem rodziców dzieci z autyzmem

Abstract: The appearance of a child with a disability is always a source of tremendous stress in the family. This problem is particularly evident in the case of an autistic child because of its unpredictable and untypical development. Every person during their life develops certain mechanisms to deal with difficult situations. According to Lazarus and Folkman (1987), dealing with stress mainly relies on specific intellectual activities and appropriate actions to control the requirements assessed by the person as burdens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…It is worth noting, however, that the difference obtained by the authors indicating that mothers of children with autism can feel much less vulnerable to parental burnout than the parents of children with moderate intellectual disabilities is the same as the specific results concerning the emotional exhaustion of mothers (Fig. 2), which obviously corresponds with the results obtained by Dudek [47].…”
Section: Discussionsupporting
confidence: 82%
“…It is worth noting, however, that the difference obtained by the authors indicating that mothers of children with autism can feel much less vulnerable to parental burnout than the parents of children with moderate intellectual disabilities is the same as the specific results concerning the emotional exhaustion of mothers (Fig. 2), which obviously corresponds with the results obtained by Dudek [47].…”
Section: Discussionsupporting
confidence: 82%
“…In times of family crisis, mothers cope worse and use emotions and avoidance behaviours [39]. In a similar study by M. Dudek (2017), among parents of children with ASD, mothers relatively more often than fathers display the avoidance-focused style (SSU) and the style of engaging in substitute activities (ACZ) [40].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…A high level of parenting stress has a negative impact on parents' ability to effectively cope with their child's behavior and the child-raising process in general [15,33]. Dudek reported that mothers of children with ASD were more likely than fathers to use avoidance and distraction coping styles [30]. Similarly, Pisula and Kossakowska drew attention to the fact that mothers of autistic children were more likely than mothers of typically developing children to experience feelings of helplessness, failure, and parenting inefficacy and to use avoidance as a coping strategy [36].…”
Section: Discussionmentioning
confidence: 99%
“…Dudek investigated coping strategies of parents of children diagnosed with autism. He discovered that Curr Probl Psychiatry 2022;23 (1) mothers of autistic children were more likely than fathers to use avoidance and distraction (engaging in substitute activities) coping styles [30]. In his study, there were no significant differences in coping styles between parents of children with autism and Asperger's syndrome [30].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation